Postnatal human enteric neurospheres show a remarkable molecular complexity - Mellein, Stefanie; Mederer, Tanja; Röth, Ralph; Günther, Patrick; Holland-Cunz, Stefan; Metzger, Marco; Samstag, Yvonne; Schröder-Braunstein, Jutta; Wabnitz, Guido H.; Kurzhals, Stefan; Scheuerer, Jutta; Beretta, Carlo Antonio; et al. (Neurogastroenterology and motility, 2019)
BACKGROUND: The enteric nervous system (ENS), a complex network of neurons and glial cells, coordinates major gastrointestinal functions. Impaired development or secondary aberrations cause severe enteric neuropathies. Neural crest-derived stem cells as well as enteric neuronal progenitor cells, which form enteric neurospheres, represent a promising tool to unravel molecular pathomechanisms and to develop novel therapy options. However, so far little is known about the detailed cellular composition and the proportional distribution of enteric neurospheres. Comprehensive knowledge will not only be essential for basic research but also for prospective cell replacement therapies to restore or to improve enteric neuronal dysfunction. METHODS: Human enteric neurospheres were generated from three individuals with varying age. For detailed molecular characterization, nCounter target gene expression analyses focusing on stem, progenitor, neuronal, glial, muscular, and epithelial cell markers were performed. Corresponding archived paraffin-embedded individuals' specimens were analyzed accordingly. KEY RESULTS: Our data revealed a remarkable molecular complexity of enteric neurospheres and archived specimens. Amongst the expression of multipotent stem cell, progenitor cell, neuronal, glial, muscle and epithelial cell markers, moderate levels for the pluripotency marker POU5F1 were observed. Furthermore, besides the interindividual variability, we identified highly distinct intraindividual expression profiles. CONCLUSIONS & INFERENCES: Our results emphasize the assessment of molecular signatures to be essential for standardized use, optimization of experimental approaches, and elimination of potential risk factors, as the formation of tumors. Our study pipeline may serve as a blueprint implemented into the characterization procedure of enteric neurospheres for various future applications.
Gesehen am 25.06.2021